2020
DOI: 10.5946/ce.2019.029
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Findings in Patients Under the Age of 40 Years with Hematochezia in Singapore

Abstract: Background/Aims: Sigmoidoscopy is performed in most medical centers to evaluate the distal colons of young adults presenting with hematochezia who are at risk of developing proximal lesions. Colonoscopies offer more complete evaluations but are associated with a higher incidence of complications and possible low yield. Methods: An analysis was conducted on colonoscopies performed in our center on patients 40 years of age or younger. The study population was subdivided into 2 age groups for analysis: <30 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Several recent studies shown usefulness of colonoscopy in patients with age < 50 years [15][16][17] . However, there are few studies which addressed usefulness of colonoscopy in patients with per rectal bleeding in patients with age < 40 years 18 . In the study from Singapore, there was 6.5% overall prevalence of colonic adenoma or carcinoma 18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies shown usefulness of colonoscopy in patients with age < 50 years [15][16][17] . However, there are few studies which addressed usefulness of colonoscopy in patients with per rectal bleeding in patients with age < 40 years 18 . In the study from Singapore, there was 6.5% overall prevalence of colonic adenoma or carcinoma 18 .…”
Section: Resultsmentioning
confidence: 99%
“…However, there are few studies which addressed usefulness of colonoscopy in patients with per rectal bleeding in patients with age < 40 years 18 . In the study from Singapore, there was 6.5% overall prevalence of colonic adenoma or carcinoma 18 . With increasing rates of sporadic colorectal carcinomas in young patients need for colonoscopy in these patients is justified.…”
Section: Resultsmentioning
confidence: 99%
“…As the polyp grows in size, it may cause intestinal symptoms including bloody stool, mucous stool, and alterations in the consistency of stool. [ 18 , 19 ] To minimize the risk of cancer, it is crucial to promptly detect and remove lesions through early clinical intervention. Currently, endoscopic techniques serve as a widely employed approach for intestinal polyp resection, exhibiting favorable efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Tang et al report an analysis on colonoscopies performed in patients aged < 40 years. 9 This single-center retrospective study included rectal bleeding in 115 and 338 patients aged < 30 and 30-39 years, respectively. The major cause of bleeding was hemorrhoids.…”
mentioning
confidence: 99%